Selecting The Optimum Project Delivery Method For Gasoline Sulfur Hydrotreating Project at Plaju and Balongan Refineries of PT Kilang Pertamina International (KPI) By Using Analytic Hierarchy Process (AHP) - Andry Achmad Bastomi; Utomo Sarjono Putro (Return : Study of Management, Economic and Bussines, 2024)
PT Kilang Pertamina International (KPI), as a subsidiary of PT Pertamina (Persero), currently operates and fully administers the refinery business subholding, intends to build new Gasoline Sulfur Hydrotreater (GSH) unit to comply with the latest government regulation for Sulphur content of Gasoline shall be adjusted maximum 50 ppm by the end of 2027. In doing the project execution, it is important to find and decide the optimum Project Delivery Method (PDM) that shall be used effectively for GSH Project at the Plaju and Balongan Refineries to achieved PT KPI ultimate goal which is OTOBOSOR (On Time, On Budget, On Specification, On Regulation). The purpose of this study is to determine the selection of the optimal project delivery method for the Petroleum Sulfur Hydrotreating project at the Plaju and Balongan Refineries of PT Kilang Pertamina International (KPI). In this study, qualitative data will be used in the analysis to provide more opportunities and space for gaining a deeper understanding of a certain subject, allowing for flexibility and exploration. Those parameters are analyzed through Pair Wise Comparation Analysis of AHP Model. Based on the analysis, the best alternative to be implemented is Co-Current DBB. In terms of sensitivity analysis, Co-Current DBB is also robust and gives a solid highest value compared with the other alternatives. Therefore, Co-Current DBB is a suitable scheme to be implemented for accelerating Project step from design bidding process until EPC Phase of GSH Project.